COMPARATIVE STUDY BETWEEN NEBULISATION WITH KETAMINE, LIGNOCAINE AND BUDESONIDE IN THE ATTENUATION OF POST-OPERATIVE SORE THROAT IN ELECTIVE SURGICAL CASES UNDER GENERAL ANAESTHESIA - Subha Teresa Jose Vazhakalayil, Sanya Varma (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Background: Postoperative operative sore throat (POST) is one of the most reported complications after endotracheal intubation post General anaesthesia with an incidence of as high as 60% which may impact patient satisfaction and increase the cost of treatment. Pharmacological interventions are aimed at prevention, amelioration of symptoms and treatment of POST. Medications suggested for this purpose include corticosteroids, topical anaesthetic sprays, NSAIDs, NMDA receptor antagonists. Nebulization has several advantages over other drug delivery methods, including being safe, easy to use, requiring less medication to produce the desired effect, and having the added benefit of reaching the lower airways. Purpose: To compare the effectiveness between nebulization with ketamine, lignocaine and budesonide in the attenuation of postoperative sore throat after oral endotracheal intubation. To assess the severity of POST and study the hemodynamic variations and side effects, if any. Methods: This is a double-blinded, randomized control study conducted in a tertiary hospital with a sample size of 150 patients undergoing elective surgeries under general anaesthesia, from various surgical departments. The study was initiated after approval by the institutional Ethics Committee for a period of two years. Results:There was a variation observed in the heart rate of all three groups. At 24 hours the mean heart rate was highest at 77.48±14.55 in the budesonide group followed by 76.10 ±14.31 in the lignocaine group and 70.82±11.04 in the ketamine group and this observation is statistically significant (p=0.05). In the ketamine group at 0 hours interval, all patients (n=50) had grade-0 sore throat, at 2 hours 2 patients progressed to grade-II & 1 patient to grade-I sore throat, at 4 hours 1 patient of grade-I & grade-II each. In the later phase at 24 hours severity of the sore throat subsided again all patients (n=50) returned to grade- 0. In the lignocaine group, most of them (n=12) had severe grade (grade-III) sore throat and it subsided as time progressed. At 0 hour 47 patients had grade-0, 1 patient grade-1 and 2 patients grade-2 sore throat. The severity of sore throat in patients progressed at 2, 4 & 6 hours and then started to subside. At 24 hours all 50 patients belonged to grade-0 level sore throat in the budesonide group. Conclusion: Sore throats were less common and less severe in Group K. With time, the frequency of postoperative problems such as nausea, vomiting, and hallucinations decreased. Budesonide nebulization was less likely to cause post-operative problems than lignocaine and ketamine. Budesonide nebulization experienced the least number of complications out of the three.